2014
DOI: 10.1002/mnfr.201300729
|View full text |Cite|
|
Sign up to set email alerts
|

Interspecies communication between plant and mouse gut host cells through edible plant derived exosome‐like nanoparticles

Abstract: Scope Exosomes, small vesicles participating in intercellular communication have been extensively studied recently; however, the role of edible plant derived exosomes in interspecies communication has not been investigated. Here, we investigate the biological effects of edible plant derived exosome-like nanoparticles (EPDEN) on mammalian cells. Methods and results In this study, exosome-like nanoparticles from four edible plants were isolated and characterized. We show that these EPDENs contain proteins, lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
610
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 476 publications
(634 citation statements)
references
References 60 publications
20
610
0
4
Order By: Relevance
“…Furthermore, they have been implicated in delivering pollen allergens to humans [94]. Other remarkable evidence has come from biomedical studies and confirms exosome-like plant vesicles from somatic material as having the capacity to deliver bioactive molecules to other organisms [95,96]. Entirely supporting our thesis (illustrated in Figure 1 in main text), this class of vesicle from unrelated plant species was shown to contain RNAs, especially small RNAs [95].…”
Section: Mechanism Of Rna Movement Between Fungi and Plantssupporting
confidence: 75%
“…Furthermore, they have been implicated in delivering pollen allergens to humans [94]. Other remarkable evidence has come from biomedical studies and confirms exosome-like plant vesicles from somatic material as having the capacity to deliver bioactive molecules to other organisms [95,96]. Entirely supporting our thesis (illustrated in Figure 1 in main text), this class of vesicle from unrelated plant species was shown to contain RNAs, especially small RNAs [95].…”
Section: Mechanism Of Rna Movement Between Fungi and Plantssupporting
confidence: 75%
“…Although this approach is promising, production of large quantities of mammalian cell nanoparticles and evaluation of their potential biohazards has been challenging. We have identified recently exosome-like nanoparticles from the tissue of edible plants including grapefruit, grapes, and tomatoes, and produced them in large quantities (1517). As with mammalian exosomes, we have demonstrated that exosome-like nanoparticles from grapes naturally encapsulate small RNAs, proteins, and lipids.…”
Section: Introductionmentioning
confidence: 99%
“…Large numbers of exosomes might then be isolated from culture or biological fluids using advanced microfluidic isolation strategies [39]. Other potential options to scale up exosomal nanocarrier production include the use of bovine milk-derived [40] or plant-derived [14,15] exosomes following biocompatibility testing.…”
Section: Future Perspectivementioning
confidence: 99%
“…Exosomes might be modified to serve as nanocarriers either endogenously at the cellular level or exogenously following cell culture production [1], collection from body fluids or even plant-based materials [14,15]. Endogenous exosome modification typically relies on molecular biology approaches to manipulate exosome components such as proteins at the source cell production level.…”
mentioning
confidence: 99%